ĐÁNH GIÁ TỶ LỆ TỒN LƯU KHÁNG THỂ IgG KHÁNG VI RÚT DENGUE, VI RÚT HANTA VÀ VI RÚT CHIKUNGUNYA TRÊN NGƯỜI KHỎE MẠNH TỪ 18 TUỔI TRỞ LÊN BẰNG KỸ THUẬT ELISA TẠI MỘT SỐ KHU VỰC THUỘC TỈNH HÀ GIANG VÀ LAI CHÂU - Lê, Thị Lan Anh; ZH.A., Kasyan; E.A. , Chumachkova; I.N., Sharova; A. M. , Porshakov; Võ, Viết Cường; Trịnh, Văn Toàn; Đào, Nguyên Mạnh; Bùi, Thị Thanh Nga; Đặng, Thị Việt Hương; và c.s. (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
SEROLOGICAL SURVEY OF DENGUE VIRUS, HANTAVIRUS AND CHIKUNGUNYA VIRUS ANTI ANTIBODIES IN RESIDENTS OF SOME DISTRICTS OF HA GIANG AND LAI CHAU PROVINCES Objectives: To assess the serological prevalence of Dengue virus, Hantavirus and Chikungunya virus in residents of some districts of Lai Chau and Ha Giang provinces. Research methods: Serum samples were collected from residents living in Lai Chau and Ha Giang, using ELISA method to detect and evaluate prevalence of viruses. Results: Among the 294 serum samples collected from Lai Chau and Ha Giang, there were 140 samples from Lai Chau, and 154 samples were from Ha Giang, in which more than half (56.46%) were female. Analysis of age characteristics of participants showed that the median age was 46.5 years, with 49.32% aged ≥ 45 years and 18-44 years age group accounts for 50.68%. Among the positive serum samples for the viruses, Lai Chau was 21.4% higher than Ha Giang (16.9%); The prevalence of each virus species showed that Dengue virus accounted for the highest rate of 11.2%, followed by Hantavirus accounts for 6.1%, and Chikungunya virus accounts for 1.7%. In addition, there were four cases of co-infection, including two cases of co-infection with Dengue virus and Hantavirus and two cases of Dengue virus and Chikungunya virus. The seropositivity note for Dengue virus in the 18-44 age group was 2.2 times higher than in the ≥ 45 age group. The seropositivity rate for Hantavirus in women was 3.9 times higher than in men. There was no relationship about seropositivity for Chikungunya virus and age or gender. Conclusions: The seroprevalence characteristics of the three viruses differed by area, gender, and age.